Linear and Third Order Non-Linear Optical Properties of Urea Salicylic Acid Crystal - Andal, C.; Murugakoothan, P. (Asian Journal of Chemistry, 2015)
An organic non-linear optical crystal urea salicylic acid was grown by slow evaporation method using the mixed solvent of ethanol and water in equal ratio. The lattice parameters of urea salicylic acid crystal were obtained by single X-ray diffraction study. The optical transmittance study revealed the good transmission window of the urea-salicylic acid and its suitability for optical applications. The non-linear refractive index, n2, absorption coefficient, b and third order susceptibility, c(3) have been measured through the Z-scan technique with He-Ne laser at 632.8 nm. The grown urea salicylic acid crystal exhibits two photon absorption and self-defocussing performance.